Influence of nitrogen deficiency on photosynthesis and chloroplast ultrastructure of pepper plants (Research Note) - Doncheca, Snejana; Vassileva, V.; Ignatov, G.; Pandev, S.; Dris, Ramdane; Niskanen, Raina (MTT Agrifood Research Finland, 2001)
Liuosviljelyssä kasvatetulla paprikalla (Capsicum annuum L. cv. Zlaten Medal) tutkittiin typen puutteen vaikutusta biomassan tuotantoon, fotosynteesiin ja kloroplastien rakenteeseen. Ilman typpilannoitusta lehtipinta-ala pieneni, biomassan kertyminen väheni ja juuren kuivapainon suhde verson kuivapainoon suureni. Typen puute heikensi fotosynteesiä alentamalla hiilidioksidin sitoutumisnopeutta ja lehtien klorofylli- ja karotenoidipitoisuutta ja aiheutti kloroplasteissa tärkkelysjyvästen ja plastoglobulien osuuden suurenemista sisäisen membraanirakenteen kustannuksella. Tulokset osoittavat, että kloroplastien rakenteen normaali muodostuminen, fotosynteesin tehokkuus ja paprikan sadon tuotto ovat riippuvaisia riittävästä typen saannista.

Pepper plants (Capsicum annuum L. cv. Zlaten Medal) were grown on nutrient solution without nitrogen, and photosynthetic response of plants was examined by determination of leaf CO2 fixation and chlorophyll and carotenoid contents. The absence of nitrogen in the medium resulted in a decrease of the leaf area and of plant biomass accumulation, and in an increase of the root-shoot dry weight ratio. The photosynthetic activity and chlorophyll and carotenoid contents decreased significantly under nitrogen deprivation. Examination of nitrogen deficient leaves by transmission electron microscopy showed dramatic changes in chloroplast ultrastructure. The proportion of starch granules and plastoglobules in the stroma matrix was increased and internal membrane system was greatly reduced. It seems that nitrogen plays an important role in the formation of chloroplast structure and hence to the photosynthetic intensity and productivity of pepper plants.
Research Note
Keywords: typpi; paprika; fotosynteesi; kloroplastit; Capsicum annuum; CO2 assimilation; leaf area; nitrogen deficiency; photosynthetic pigments; plastoglobules; starch